2022
DOI: 10.18203/2394-6040.ijcmph20222229
|View full text |Cite
|
Sign up to set email alerts
|

Human consumption, nutritional value and health benefits of Moringa (Moringa oleifera Lam.): a review

Abstract: Moringa is an expeditious-growing evergreen perennial plant and has wide adaptability to grow in different environmental conditions. The nutritive value and medicinal benefits of its leaves, flowers, pods, roots, and stem barks are established by philanthropic research. Edible parts are rich in protein, vitamins, minerals, antioxidants, and other chemical compounds with medicinal properties. The pods and leaves are mainly used as vegetables and ingredients in soups and curries. It is used to boost the nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…The dragon fruit cultivation area is expanding rapidly in many countries due to its economic potential and nutritional benefit (Hossain et al, 2021), attracting interest from countries such as the United States, Australia, Southeast Asia, Israel, and other regions (Jalgaonkar et al, 2022). Pitahaya mayor importers are the United States, Japan, European Union and Canada, while major exporters are: Israel, Mexico and Nicaragua, in addition, Colombia participate with 38% of the international exportations (AGRONET, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The dragon fruit cultivation area is expanding rapidly in many countries due to its economic potential and nutritional benefit (Hossain et al, 2021), attracting interest from countries such as the United States, Australia, Southeast Asia, Israel, and other regions (Jalgaonkar et al, 2022). Pitahaya mayor importers are the United States, Japan, European Union and Canada, while major exporters are: Israel, Mexico and Nicaragua, in addition, Colombia participate with 38% of the international exportations (AGRONET, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Boyapati et al (2022) reported DPPH inhibition of around 69.6% and the polyphenol content as 96.7 mg GAE/g, in pitaya seed oil. The pitaya fruit may be thought to a more significant amount of antioxidants when compared to other subtropical fruits like mango and pineapple (Farid Hossain et al 2021). Seeds from other fruits, such as grape seeds, and berries, and from the Cactaceae family also Opuntia spp.…”
Section: Resultsmentioning
confidence: 99%
“…Dragon fruit is a notable source of carbohydrates, with a concentration ranging from 8.0 to 18.0 g/100 g. This is comparable to bananas, which contain 22.8 g/100 g of carbohydrates, and higher than apples (11.4 g/100 g) and oranges (8.5 g/100 g) [ 38 ]. This is comparable to vegetables such as potatoes, which contain 17.5 g/100 g of carbohydrates [ 39 ].…”
Section: Relevant Cacti For Food Industrymentioning
confidence: 99%